Total bilateral hip arthroplasty in one surgical procedure - Popović Zoran; Rajović Jovo; Radunović Aleksandar (Vojnosanitetski Pregled)
Background/Aim. Primary coxarthrosis occurs often in older population. There is possibility of implanting both endoprothesis simultaneously in bilateral coxarthrosis which decreases hospitalization and reduces the expenses and possibility of complication that can occur during general anesthesia. The most serious indications for bilateral total hip arthroplasty in one procedure are younger patients with serious bilateral osteoarthrosis of the hips, without added diseases. Absolute contraindication is found in patients with persistent ductus arteriosus and septal defect. The aim of this study was to point out the possibility and advantages of a single-staged bilateral hip arthroplasty and introducing it in our orthopedic practice. Methods. The procedure was accomplished in 19 patients. The standard total hip arthroplasty surgical technique was performed, followed by the usual antibiotic and anticoagulant therapy. Results. Only one complication - acetabular part instability we recorded, followed by luxation that was surgically managed. Conclusion. This procedure can be performed routinely in selected population and should be reserved for major medical centers capable to provide adequate postoperative care.